The Sensitivity of Satellite Solar‐Induced Chlorophyll Fluorescence to Meteorological Drought - Wenzhe Jiao; Qing Chang; Lixin Wang (Earth's Future, 2019)
Abstract Solar‐induced chlorophyll fluorescence (SIF) could provide information on plant physiological response to water stress (e.g., drought). There are growing interests to study the effect of drought on SIF. However, to what extent SIF responds to drought and how the responses vary under different precipitation, temperature, and potential evapotranspiration conditions are not clear. In this regard, we evaluated the relationship between satellite‐based SIF product and four commonly used meteorological drought indices (Standardized Precipitation‐Evapotranspiration Index, Standardized Precipitation Index, Temperature Condition Index, and Palmer Drought Severity Index) under diverse climate regions in the continental United States. The four drought indices were used because they estimate meteorological drought conditions based on either single or combined meteorological factors such as precipitation, temperature, and potential evapotranspiration, representing different perspectives of drought. The relationship between SIF and meteorological drought varied spatially and differed for different ecosystem types. The high sensitivity occurred in dry areas characterized by a high mean annual growing season temperature and low vegetation productivity. Through random forest regression analyses, we found that temperature, gross primary production, precipitation, and land cover are the major factors affecting the relationships between SIF and meteorological drought indices. Taken together, satellite SIF is highly sensitive to meteorological drought, but the high sensitivity is constrained to dry regions.